Metode Hamamun Sebagai Salah Satu Bentuk Adaptasi Kurikulum pada Materi Bilangan Bulat: - - Sutarti, S; Andini, Dinar Westri; Irfan, Muhammad (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
In reality, teachers are faced with a diversity of student characteristics, one of which is related to different cognitive abilities. The aim of this research is to determine the successful learning outcomes of all students through the implementation of the Hamamun method "Only Forward and Backward". This research method uses a case study approach in the form of a one shot case study. The subjects in this research were class VI students at SD Negeri Demakijo 2. The research was carried out by providing action in the form of applying the Hamamun method and after that observation, interviews and documentation of student learning outcomes were carried out. The steps for using the Hamamun method include: planning, action and reflection carried out in blended learning. The research results showed that there was an increase in student learning outcomes from the initial conditions and after implementing the Hamamun Method. In the initial conditions, students experienced limitations in understanding the arithmetic operations of adding and subtracting integers. By using the Hamamun method, the achievement of learning completion reaches 100%, with the average final score of class VI students being 90.96 and the average achievement being 78.00. This proves that the Hamamun method is an alternative learning method to meet the diversity of students, especially the diversity of different cognitive abilities.